Structural/Functional Matches and Divergences of Phytoprostanes and Phytofurans with Bioactive Human Oxylipins - Sonia Medina; Ángel Gil-Izquierdo; Thierry Durand; Federico Ferreres; Raúl Domínguez-Perles (MDPI AG, 2018)
Structure-activity relationship (SAR) constitutes a crucial topic to discover new bioactive molecules. This approach initiates with the comparison of a target candidate with a molecule or a collection of molecules and their attributed biological functions to shed some light in the details of one or more SARs and subsequently using that information to outline valuable application of the newly identified compounds. Thus, while the empiric knowledge of medicinal chemistry is critical to these tasks, the results retrieved upon dedicated experimental demonstration retrieved resorting to modern high throughput analytical approaches and techniques allow to overwhelm the constraints adduced so far to the successful accomplishment of such tasks. Therefore, the present work reviews critically the evidences reported to date on the occurrence of phytoprostanes and phytofurans in plant foods, and the information available on their bioavailability and biological activity, shedding some light on the expectation waken up due to their structural similarities with prostanoids and isoprostanes.